Intimate partner violence among reproductive-age women in central Gondar zone, Northwest, Ethiopia: a population-based study - Wondale Getinet; Telake Azale; Eskedar Getie; Endalamaw Salelaw; Tadele Amare; Demeke Demilew; Alemu Lemma; Destaw Kibret; Abayneh Aklilu; Techalo Tensae; Mengesha Srahbzu; Shegaye Shumet (BMC, 2022)
Abstract Background Violence against women is the most widespread kind of human rights violation, and it has been linked to a wide range of consequences. The most prominent psychosocial and mental health concern that has serious effects for women's physical and mental well-being. This study assessed the prevalence and associated factors of women's violence by intimate partner among women in the reproductive age group (15-49). Methods Multistage community-based cross-sectional study was conducted among reproductive age group women in the central Gondar zone. We recruited 845 participants and interviewed by health extension workers using face-to-face interviews. We used a Women's Abuse Screening test to outcome variable; it has a total score ranges 0-16, a score > 1 indicates positive for the presence of intimate partner violence within a year. Variables were coded and entered to Epi data version 3.1 and exported to SPSS version 21 for analysis. Descriptive statistics and multivariate logistic regression analysis was run for data analysis. Adjusted odds ratios (AOR) with a 95% confidence level (CI) were declared significant. Result Among a total of 845 participants 804 responded to the interviews with a response rate of 95%. The prevalence rate of intimate partner violence is 391(48.6%). From multivariate logistic regression analysis women being married [AOR:3.85; 95% CI (2.38, 6.22)], high school and above educational status [(AOR: 0.43; 95% CI (0.30, 0.61), women's having > 3children [(AOR: 1.82, 95% CI (1.0, 3.1)], having a household food insecurity[(AOR: 2.09, 95% CI (1.51, 2.91)], having life threatening events [(AOR: 2.09; 95% CI (1.51, 2.91)], moderate social support [(AOR: 0.60; 95% CI (0.41, 0.83)], depression [(AOR: 3.12; 95% CI (1.60, 6.07) were significantly associated with violence by intimate partner at 95% CI . Conclusion Intimate partner violence is common among reproductive-age women. Married, women with several children, food insecurity, life-threatening events, and depression were all found to be significant predictors of violence. Measures should be taken to raise community awareness, particularly among intimate partners, their families, and government officials.